Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have tried using the change of base formula, but can't quite complete the equality:

$$ a^{\log{b}} \\ a^{\frac{\log_a{b}}{\log_a{a}}} $$

How do I get the base of the exponent to be b?

share|cite|improve this question

3 Answers 3

up vote 4 down vote accepted

Since $x = e^{\log x}$

\begin{align*} a^{\log b} = \left(e^{\log a}\right) ^{\log b} = e^{\log a \log b} = e^{\log b \log a} = \left(e^{\log b}\right)^{\log a} = b^{\log a} \end{align*}

share|cite|improve this answer

Let $x=a^{\log b}$ and $y=b^{\log a}$. Then $\log x= \log a$. $\log b= \log y$. So, $x=y$.

share|cite|improve this answer

Let (capital) $B$ be the base of the logarithms. Then $$ a^{\log_B b} = \Big(B^{\log_B a}\Big)^{\log_B b} = B^{(\log_B a)(\log_B b)}, $$ and that is clearly symmetric in $a$ and $b$. Or you could just go on from there: $$ \cdots= \Big(B^{\log_B b}\Big)^{\log_B a} = b^{\log_B a}. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.